Parâmetros termodinâmicos da casca de laranja desidratada - Santos, Carolina M. [UNESP]; Morais, Leandro Cardoso de [UNESP] (Soc Brasileira Quimica, 2015)
The global energy scenario is currently a widely discussed topic, with growing concern about the future supplies. Thus, much attention has been dedicated to the utilization of biomass as an energy resource. In this respect, orange peel has become a material of great interest, especially to Brazil, which generates around 9.5 million tons of this waste per year. To this end, the authors studied the kinetics of the thermal processing of dried orange peel in inert and oxidizing atmosphere. The thermodynamic parameters were determined by the Ozawa-Flynn-Wall method for the global process observed during heating from the 25 degrees C up to 800 degrees C. The thermal analysis in air and nitrogen showed 3-2 stages of mass loss, respectively, with approximately 20% residual mass under a nitrogen atmosphere. The increase in the values of activation energy for the conversion points between 20% and 60% for thermal effects in air and nitrogen atmosphere was observed. The activation energy obtained in an oxidizing atmosphere was higher than that obtained under a nitrogen atmosphere. The fourier-transform infrared spectroscopy and X-ray diffraction analysis showed that the material has a high level of complexity with the presence of alkali and alkaline earth groups as well as phosphate, plus substances such as pectin, cellulose and lignin.
Thermodynamic parameters of dehydrated orange peel
Keywords: Thermodynamic parameters; Fruit residue; Thermogravimetry; Activation energy; Biofuel